The role of state government accountability in the management of political violence in Nigeria - Ilelah, Kabiru Bello; Ab Halim, Adlina; Ismail, Mohd Mahadee; Md Nor, Mohd Sabri (Human Resource Management Academic Research Society, 2022)
Accountability enhances citizens’ trustworthiness and legitimacy towards the government. Bauchi state government in Nigeria has been facing challenges in managing political violence due to a lack of proper accountability. As such state government loses the expected legitimacy from its citizens. Literature shows scanty research on state government accountability, especially on political violence management. Therefore, this study explores state government commitment toward accountability in managing political violence. The research applied good governance theory to guide the research. A qualitative method based on a case study approach was employed. Purposive and snowballing sampling techniques were used to identify informants. A total number of 17 informants which includes government officials, security personnel, community leaders, members of the NGOs, peace ambassadors, victims, and academicians. Data were collected through in-depth interviews. The data obtained were analyzed, and presented based on themes. The result reveals that state government responsibility in managing political violence is inadequately implemented. The findings further shows that there are cases of irrational justification for government action and in-action concerning the management of political violence. Based on this, there is the need for the government to be proactive in its commitment towards accountability. The research highlighted the major factors affecting accountability in governance.